Wireless networks for traffic light control on urban and aerotropolis roads - Cunha, João (2021)
This paper presents a traffic lights system based on wireless communication, providing a support infrastructure for intelligent control in smart cities and aerotropolis scope. An aerotropolis is a metropolitan subregion which infrastructure is centered around an airport [1]. Traffic intensity is increasing all over the world. Intelligent dynamic traffic lights system control are sought for replacing classic conventional manual and time based systems. In this work a wireless sensors network is designed and implemented to feed real time data to the intelligent traffic lights systems control. A physical prototype is implemented for experimental validation outside laboratory environment. The physical prototype shows robustness against unexpected issues or local failures. Results are positive in the scope of the experiences made and promising in terms of extending the tests to larger areas.